Knowledge management practices and innovation outcomes: The moderating role of risk-taking and proactiveness - Gema García-Piqueres; Ana-M. Serrano-Bedia; Marta Pérez-Pérez (Administrative Sciences, 2019)
This study, by the application of a linear regression by ordinary least squares (OLS), aimed to explore the relationships between knowledge management practices (KMP) and innovation outcomes (product, process, organizational, and commercial), and howthey can bemoderated by two dimensions of the entrepreneurial orientation (proactiveness and risk taking). This empirical study used survey data from a sample of 288 Spanish family small and medium enterprises (SMEs). The results revealed a positive effect of all the KMPs studied for at least one of the innovation variables studied. Regarding the moderating effect of proactiveness and risk taking on the KMP-innovation outcomes relationship, proactiveness negativelymoderated the relationship between knowledge creation and product/process innovation. Moreover, a positive moderating effect was found for the case of knowledge application and process innovation. With regard to risk taking, the evidence found was mixed, and confirmed for some KMPs and all the innovation measures, with the exception of process innovation. The only positivemoderating effect foundwas for knowledge storage and product innovation,whereas, contrary to expected, a negative moderating effect was found for knowledge creation, transfer, and application practices and commercial, product, and organizational innovations, respectively.
Keywords: 350; family firm; knowledge; innovation outcomes; risk-taking; proactiveness